(untitled) (Journal of the College of Basic Education, 2022)
The harsh nature of life that the Mongols lived in Mongolia made them one of the harshest peoples, and the most tolerant of hunger and difficult conditions, and the Mongol tribes witnessed conflict among themselves, which made them combative tribes of the first class, used by neighboring countries as mercenaries in their armies such as the Krait, And Karakhtai.And a unique personality, Genghis Khan, was able to direct this endless Mongol cruelty towards the world around them, and as far as possible to reach it with the aim of controlling all the trade routes that were known at the time, especially the Silk Road, while making this cruelty non-existent among them through The norms that he framed in the form of laws, which were known as despair, and which made them an obedient tool in his hands, and at the same time a sword drawn over the necks of the peoples they conquer.